Analysis of willingness to pay in improving the quality of biopesticide products based on green economy - Fitriyani, Zenita Afifah; Putra, Dimas Ganda Permana; Ardiyanto, Fahrur Rijal; Dewi, Yuni Rosita; Khusumawati, Titik (Journal of Economics Research and Policy Studies, 2024)
This study aims to estimate the value of Willingness to Pay and identify the influence of factors on WTP in improving the quality of green economy-based biopesticide products in Candiwatu Village, Pacet District, Mojokerto Regency. The method used is quantitative descriptive analysis with the Accidental Sampling technique. Data analysis was carried out using the Contingent Valuation Method and multiple linear regression. The results of the study showed that the average additional nominal that the community was willing to pay for quality green economy-based biopesticide products was IDR 32,000. From the multiple linear regression test, it was found that partially three variables that significantly influenced WTP were agricultural land area, income, and biopesticide product quality. Simultaneous testing showed that all variables had a significant influence on WTP. These findings indicate that the community has a willingness to pay to support the use of environmentally friendly products that can increase the proportion of sustainable fertilizers, with income, land area, and product quality being the main aspects driving the decision.